(untitled) (American Journal of Technology and Applied Sciences, 2025)
The article discusses the device of independent ventilation ducts from the chamber to the ventilated room and high-rise buildings with a large number of floors. The exchange rate in kitchens and sanitary facilities should be taken according to calculations and determination of the cross-section of the supply and exhaust ventilation ducts in high-rise buildings